Pendekatan Rational Emotive Behaviour Therapy (REBT) Terhadap Pasien Post Traumatic Stress Disorder (PTSD) - Fikran Omar; Randa Putra Kasea Sinaga (Yayasan Literasi Sains Indonesia, 2022)
Humans are inherently unique and have a tendency to think rationally and irrationally. When people think and act rationally, humans will be effective, happy, and competent. Conversely, when thinking and behaving irrationally, individuals will become ineffective. A person's emotional reaction to a situation/event is largely due to conscious or unconscious evaluations, interpretations, and philosophies. Psychological or emotional barriers are the result of illogical and irrational ways of thinking. Emotions accompany individuals who think with prejudice, are highly personal, and irrational. Irrational thinking begins with learning illogically obtained from parents and the culture in which they grew up. Thinking irrationally will be reflected in the verbalization used. Illogical verbalizations indicate wrong ways of thinking and proper verbalizations show correct ways of thinking. This research activity is a form of implementing counseling practices with a Rational Therapy approach to people with mental disorders, in this case, Post Traumatic Stress Disorder (PTSD) at Yayasan Satu Hati Membangun (YASAM).